An explanation for the lower payoff to schooling for immigrants in the Canadian labour market - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2009)
This paper examines the difference between the payoffs to schooling for immigrants and the native born in Canada, using 2001 Census data. Analyses are presented for males and females. Comparisons are offered with findings for the US. The paper uses the Overeducation/Required education/Undereducation framework (Hartog, 2000) and a decomposition developed by Chiswick and Miller (2008). This decomposition links overeducation to the less-than-perfect international transferability of immigrants' human capital, and under-education to favourable selection in immigration. The results show that immigrants have a lower payoff to schooling because of the different effects under-education and over-education have on their earnings. The effects of under-education, or selection in immigration, are, however, twice as large as the effects of over-education, or limited international transferability of human capital. Favourable selection in immigration appears to be less important in Canada than in the US, where it predominates among the least educated.
urn:nbn:de:101:1-200910141279
Keywords: I21; J24; J31; J61; F22; 330; Immigrants; skill; schooling; earnings; rates of return; Canada; Migranten; Qualifikation; Bildungsertrag; Überqualifikation; Geschlecht; Vergleich; Kanada